2015
DOI: 10.1080/15275922.2015.1059390
|View full text |Cite
|
Sign up to set email alerts
|

Online Water Monitoring Method as a Water Security Tool: A Feasibility View

Abstract: Since the tragic event on September 11, 2001 (9/11), homeland security has been the center of major attention not only in the United States but also around the world. Among homeland security agenda, more concerns on drinking water system have been drawn into the forefront attention from the public and water industry. Governmental agencies have been called upon to strongly protect the water resources from becoming a possible terror target. The online monitoring of a water system offers the potential to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Westphal, Chapra, and Sung () demonstrated that TOC and UV 254 correlated significantly, resulting in the development of a model that was successful in predicting a drinking water reservoir's chlorination rates and DBP formation potentials. Online instrumentation for monitoring TOC and UV 254 has been demonstrated to be useful as a security tool (Cho, Kim, Park, & Gil, ), as well as a predictive indicator of TTHMs (Wert, Bolding, Rexing, & Zegers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Westphal, Chapra, and Sung () demonstrated that TOC and UV 254 correlated significantly, resulting in the development of a model that was successful in predicting a drinking water reservoir's chlorination rates and DBP formation potentials. Online instrumentation for monitoring TOC and UV 254 has been demonstrated to be useful as a security tool (Cho, Kim, Park, & Gil, ), as well as a predictive indicator of TTHMs (Wert, Bolding, Rexing, & Zegers, ).…”
Section: Introductionmentioning
confidence: 99%